2012
DOI: 10.1007/s11926-012-0290-2
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α Blocker Therapy and Solid Malignancy Risk in ANCA-Associated Vasculitis

Abstract: ANCA-associated vasculitides (AAV) are small vessel systemic vasculitis syndromes associated with the potential for high morbidity and mortality. This group includes granulomatosis with polyangiitis (Wegener´s, GPA), microscopic polyangiitis (MPA), and eosinophilic granulomatosis with polyangiitis (Churg-Strauss, EGPA). The standard treatment consists of a combination of glucocorticoids and potent immunosuppressant drugs. These have broad mechanisms of action as well as important adverse effects. Efforts have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…Currently, the monoclonal antibodies, rituximab, and mepolizumab have been reported as novel drugs in AAVs treatment [11,12]. Our previous data confirmed that TNF-α blockers in rheumatic diseases e. g. rheumatoid arthritis compromised the disease activity [13] whereas, TNF-α blocker, etanercept characterized by increasing solid malignancies development [14].…”
Section: Introductionsupporting
confidence: 69%
“…Currently, the monoclonal antibodies, rituximab, and mepolizumab have been reported as novel drugs in AAVs treatment [11,12]. Our previous data confirmed that TNF-α blockers in rheumatic diseases e. g. rheumatoid arthritis compromised the disease activity [13] whereas, TNF-α blocker, etanercept characterized by increasing solid malignancies development [14].…”
Section: Introductionsupporting
confidence: 69%
“…These data suggest a unique functional role for domain III, which may be employed as a ligand receiving pocket such as EGFR, HER3, and HER4. Ligand-induced activation of EGFR involves a marked change in the extracellular region from a 'tethered' (inactive) to an 'extended' (active) configuration, 27 in which an exposed 'dimerization arm' in domain II drives the formation of receptor dimers. 28 In tethered EGFR, the dimerization arm is occluded by auto-inhibitory intramolecular interactions between domains II and IV, which are also observed in unliganded ErbB3 and ErbB4 but are absent in ErbB2.…”
Section: Discussionmentioning
confidence: 99%
“…It is proposed that TNF-alpha inhibitors enhance malignant growth via the blockage of TNF-alpha and its anti-tumoral mechanisms. [12][13][14] An experimental animal tumour model demonstrated that anti-TNF alpha antibodies hindered anti-tumour immune responses and promoted the growth of immunogenic rat colon tumours that were rejected by immunocompetent untreated rats.…”
mentioning
confidence: 99%